Case Report: Prolonged clinical benefit with sequential trastuzumab-containing treatments in a patient with advanced extramammary Paget disease of the groin - Zattarin, Emma; Nichetti, Federico; Ligorio, Francesca; Mazzeo, Laura; Lobefaro, Riccardo; Fucà, Giovanni; Peverelli, Giorgia; Vingiani, Andrea; Bianchi, Giulia V.; Capri, Giuseppe; de Braud, Filippo; Vernieri, Claudio (Frontiers in Oncology, 2022)
Extramammary Paget Disease (EMPD) is a rare form of cutaneous, intraepithelial adenocarcinoma which typically presents itself as an erythematous plaque originating from apocrine-gland rich regions, such as the vulva, the perianal region, the scrotum, the penis, or the axilla. EMPD patients typically have a good prognosis, with expected 5-year survival of 60-92%, but it is estimated that about one-third of EMPD patients will develop lymph-node or distant metastases. Treatment approaches for EMPD include locoregional therapies such as broad surgical resection and radiotherapy, when the disease is localized, as well as chemotherapy and biological agents for advanced EMPD. We report the case of a 58-year-old man diagnosed with locally advanced, symptomatic HER2-overexpressing, AR-positive EMPD, who achieved long-term tumor control with a sequence of several trastuzumab-based treatments (more than 30 months with second-line carboplatin plus paclitaxel plus trastuzumab followed by trastuzumab maintenance; 9 months for third line vinorelbine plus trastuzumab). Even if it is reported that AR expression occurs concomitantly with HER2 overexpression in more than half of the cases of EMPD, to the best of our knowledge this is the first case report describing androgen receptor blockade therapy in combination with an anti-HER2 agent. Our patient did not benefit from androgen receptor blockade in combination with trastuzumab, thus suggesting that AR expression may simply reflect an intrinsic characteristic of the EMPD cell of origin, rather than tumor dependence upon AR signaling. Given the reported sensibility to anti-HER2 therapy, also new antibody drug conjugates targeting HER2 are worth exploring in the management of advanced EMPD.